Al-Farabi and turkish judz (Journal of actual problems of jurisprudence, 2019)
The article to derivate of al-Farabi’s learning and Turkish judz inner logistic contacts is devoted. The author concentrating on thedefi nition “city” in al-Farabi works what may be reconstructed later in Turkish role’s tradition.